2020
DOI: 10.3762/bjnano.11.91
|View full text |Cite
|
Sign up to set email alerts
|

Monolayers of MoS2 on Ag(111) as decoupling layers for organic molecules: resolution of electronic and vibronic states of TCNQ

Abstract: The electronic structure of molecules on metal surfaces is largely determined by hybridization and screening by the substrate electrons. As a result, the energy levels are significantly broadened and molecular properties, such as vibrations are hidden within the spectral line shapes. Insertion of thin decoupling layers reduces the line widths and may give access to the resolution of electronic and vibronic states of an almost isolated molecule. Here, we use scanning tunneling microscopy and spectroscopy to sho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 64 publications
1
12
0
Order By: Relevance
“…Single-molecule prototypes or molecular nanostructures are often prepared on metals, which usually provide a sufficiently low diffusion barrier for efficient self-assembly and simultaneously allow for in-depth analysis through atomically precise tools from the family of scanning probe microscopes [1][2][3]. At the same time, however, metallic substrates usually influence the properties of adsorbed molecular species, leading to hybridization, charge transfer, or screening at the interface [4][5][6]. Also, metallic surfaces may provide relatively weak binding, dominated by van der Waals interactions [7], but the lack of a gap results in broadening and shifting of the molecular resonances.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single-molecule prototypes or molecular nanostructures are often prepared on metals, which usually provide a sufficiently low diffusion barrier for efficient self-assembly and simultaneously allow for in-depth analysis through atomically precise tools from the family of scanning probe microscopes [1][2][3]. At the same time, however, metallic substrates usually influence the properties of adsorbed molecular species, leading to hybridization, charge transfer, or screening at the interface [4][5][6]. Also, metallic surfaces may provide relatively weak binding, dominated by van der Waals interactions [7], but the lack of a gap results in broadening and shifting of the molecular resonances.…”
Section: Introductionmentioning
confidence: 99%
“…Different insulating films have already been applied, ranging from ionic salts such as NaCl [ 8 9 ], KCl [ 10 11 ], or KBr [ 12 ], through oxide [ 13 ] or nitride [ 14 ] layers to molecular wetting layers [ 15 ] and two-dimensional materials, such as graphene [ 16 17 ], hBN [ 11 , 18 ], or even organic layers [ 19 ]. Recently, it has been proposed that a monolayer of transition metal dichalcogenides, for example, MoS 2 , may play a similar role [ 4 , 20 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…To simulate the d I /d V spectrum, we considered individual and coupled modes with a significant Huang–Rhys factor, i.e., higher harmonics of individual and coupling of different modes and their harmonics (“progression of progressions”). Then, the intensities were convoluted with a Lorentzian lineshape. , A set of spectra with different Lorentzian widths is shown in Figure c (green). The best agreement with the experimental lineshape of the LUMO and LUMO + 1 (consisting of a broad peak and a shoulder) is obtained when applying a Lorentzian width of 65 mV (half-width at half-maximum).…”
Section: Resultsmentioning
confidence: 85%
“…Then, the intensities were convoluted with a Lorentzian lineshape. 59 , 67 A set of spectra with different Lorentzian widths is shown in Figure 3 c (green). The best agreement with the experimental lineshape of the LUMO and LUMO + 1 (consisting of a broad peak and a shoulder) is obtained when applying a Lorentzian width of 65 mV (half-width at half-maximum).…”
Section: Resultsmentioning
confidence: 99%
“…The semiconducting 2D material MoS 2 may act as a decoupling layer for molecules from the underlying metal substrate if the molecular resonances lie within the MoS 2 bandgap. Hence, Yousofnejad et al [ 85 ] found using MoS 2 on Ag(111) as substrate that the HOMO of tetracyanoquinodimethane (TNCQ) is not decoupled because it is located in the MoS 2 valence band, while the lowest unoccupied molecular orbital narrows but still suffers from lifetime broadening because it is situated at the conduction band onset of MoS 2 . Despite this, the vibronic states of the transiently negatively charged TCNQ could be resolved by STS.…”
mentioning
confidence: 99%